Reexamination of the taxonomic status of Coladenia agni (de Nicéville, [1884]) from Hainan, China reveals a new subspecies (Lepidoptera, Hesperiidae) - Li, Hua-Zhao; Liu, Zhe; Li, Jia-Ling (Zootaxa, 2024)
By reexamining the taxonomic status of Coladenia agni (de Nicéville, [1884]) from different localities, the insular population from Hainan Island is described as a new subspecies, i.e., C. a. huanghaoi Li & Liu ssp. nov., based on morphological and genetic distinctions. The habitus, distributional map, and molecular phylogeny of all subspecies of C. agni are provided with remarks on ssp. sundae de Jong & Treadaway, 1992. Furthermore, some less-discussed characteristics on the hind tibiae are also illustrated and discussed.